2014
DOI: 10.1002/smll.201401040
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Differentiation of Human Embryonic Stem Cells as Microscaled Multilayered Colonies Leading to Enhanced Homogeneity and Maturation

Abstract: Directed differentiation of human embryonic stem cells (hESCs) towards hepatocyte-like cells on planar tissue culture plates has been extensively investigated with great promise to provide alternative cell sources for drug metabolism/toxicity testing. Recently, hepatic differentiation of hESCs in 3D configuration with better mimicry of embryonic liver development represents incremental efforts to improve the differentiation efficiency and cellular maturation. However, most of the present 3D differentiation con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
(55 reference statements)
1
22
0
Order By: Relevance
“…We concluded for the clump culture that the 200 nm substrate improved DE differentiation of hESCs predominantly through effective cell–nanofiber contact rather than providing 3D cell–cell contacts by spheroid formation. A similar conclusion was reached in a recent study where the formation of multilayered colonies by micropatterned substrates was shown to have no significant effect on DE differentiation of hESCs compared to monolayer colonies …”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…We concluded for the clump culture that the 200 nm substrate improved DE differentiation of hESCs predominantly through effective cell–nanofiber contact rather than providing 3D cell–cell contacts by spheroid formation. A similar conclusion was reached in a recent study where the formation of multilayered colonies by micropatterned substrates was shown to have no significant effect on DE differentiation of hESCs compared to monolayer colonies …”
Section: Resultssupporting
confidence: 87%
“…Since nanotopography-mediated spheroid formation has been reported to support maintenance of hESC pluripotency, [39][40][41] the newly formed 3D cell-cell contacts on 200 nm nanofibers could be considered as a favorable event which might prevent non-desirable early differentiation during the three-day expansion and subsequently present a more homogeneous population for endodermal induction. 42 By DE differentiation, hESCs undergo epithelial-to-mesenchymal transition processes 38 where cells assume a mesenchymal, migratory phenotype which might flatten the colony and increase cellsubstrate interactions. 43 In order to investigate whether the multilayered colonies that formed on the 200 nm substrate could switch to a more spread shape upon differentiation, we analyzed SEM images of the differentiated colonies.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…115 Under this view, hepatic differentiation was performed in differently scaled 3D culture models. Microscale approaches are mainly based on 3D cell aggregation in matrices like collagen, 116 alginate, 117 hydrogel, 118 or Matrigel. 119 Liver-specific parameters, such as albumin production, urea secretion, and CYP expression indicate a higher grade of hepatic differentiation in these models when compared to conventional 2D cultures.…”
Section: Human Pluripotent Stem Cellsmentioning
confidence: 99%
“…However, one of the remaining questions that arises when using HLCs derived from PSCs is the stability of their phenotype and function in long-term cultures, a problem commonly encountered with cultured adult hepatocytes (Schwartz et al 2014). Hence, distinct strategies to improve and stabilize the hepatic phenotype of derived HLCs, such as employing complex 3D culture systems (spheroidal aggregates, perfused bioreactors) (Sivertsson et al 2013;Gieseck et al 2014;Sengupta et al 2014;Subramanian et al 2014;Takayama et al 2014;Yao et al 2014;Kim et al 2015) or using different extracellular matrices (Hay et al 2011), have been promoted.…”
Section: Phenotypic Stability Expansion and Cryopreservationmentioning
confidence: 99%